Development of tomato harvester robotic arm prototype using IoT application - Yusof, N.; J. Ja’afar, A.; MD Yunos, N.; Razali, S. (International Journal of Engineering and Technology, 2019)
In order to replace harvesting tomato manually, a robotic arm prototype for harvesting tomatoes using Internet of things (IoT) is presented in this paper. The objective to develop a robotic arm prototype which works autonomously is achieved. Due to the lack and high cost of labour, acrylic plastic materials prototype robot that controlled by Rasberry Pi3 is used for tomato recognition and localization. A coordinate or location used to pick tomatoes is identified. The usage of hue-saturation-value (HSV) colour could improve the harvesting efficiency. The movement of the actuator or the robotic arm from the initial position to the targetâ€™s position is adopted to increase the accuracy of the targeted tomato. Concerning the control software, a graphic user interface is designed to submit the operatorâ€™s commands and display the output. The performances of the robotic arm are shown.Â